Epidemiological study of burns at the Hospital of Clinics, Federal University of the Triângulo Mineiro - Anderson José Gonçalves; Marco Tulio Rodrigues da Cunha; José Fernandes dos Santos (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: Burns are a serious public health problem. Knowledge of the main epidemiological data of affected patients is paramount for preventing and establishing the best clinical treatment for these individuals. The objective was to survey the epidemiological profile of burns, the main mechanisms involved, treatments, and outcomes of these cases at the Hospital de Clínicas da UFTM. Methods: This is a retrospective and cross-sectional study of hospitalizations for burns at HC-UFTM from January 2015 to December 2019. Gender, age, depth of burns, location, etiology, use of opioids, hospitalization duration, outcome (hospital discharge or death), and extent of burned areas (EBA%). Results: This study was composed of 138 patients, divided into three groups: group 1 (G1), 39 patients; group 2 (G2), 89 participants, of which 5 died; and group 3 (G3), 10 participants, 4 of whom died. As for the trauma mechanism, the most common was scald (17.39%), followed by thermal burn (13.76%), alcohol (8.69%), and electric burns (5.79%). Conclusion: There was a higher prevalence of second-degree burns in male patients. The most prevalent mechanism of trauma was scald, and the EBA had an average of 23.9%. The face and neck were the most affected segments, and 61.59% of the patients required opioids during hospitalization. Regarding the outcome, 91.30% of patients were discharged from the hospital, and 6.52% died, with most cases in G2.